História, arqueologia e a cronologia do Êxodo : historiografia e problematizações - Berlesi, Josué (2007)
Recent academic researches brought doubts to certain parts of the History of ancient Israel. And also, there isn t an agreement about the History of Hebrew people. Thus, this research is taking into consideration a significant part of the historiography of an important event of their history: the exodus. The first part of this research concerns about how this event was interpreted in theological environments. Aiming for that, books from maximalists researchers, notably conservatives, and books from the historical critical method followers are used. The second part investigates how the exodus was interpreted outside the theological environment, emphasizing mainly historians and archaeologists books. In both parts it s considered aspects like the previous events of the exodus, it s evidences and it s route. The last part, however, concerns specifically about the exodus cronology emphasizing the main dates proposed for this event. Althoug, above that, it s recognizable the effort to detect the historical possibility of the exodus. And also, the effort to explain how did the exodus assume such great importance in the ancient israelite tradition.